2019
DOI: 10.1038/s41598-019-40616-4
|View full text |Cite|
|
Sign up to set email alerts
|

Domestic cats (Felis catus) discriminate their names from other words

Abstract: Two of the most common nonhuman animals that interact with humans are domestic dogs ( Canis familiaris ) and cats ( Felis catus ). In contrast to dogs, the ability of domestic cats to communicate with humans has not been explored thoroughly. We used a habituation-dishabituation method to investigate whether domestic cats could discriminate human utterances, which consisted of cats’ own names, general nouns, and other cohabiting cats’ names. Cats from ordinary house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 35 publications
0
10
1
Order By: Relevance
“…More specifically, house cats -with a closer relationship with their owner -should show stronger results than cats living at a cat café where many people interact with them each day. In previous research data from these two groups of cats analyzed separately their responses to human voices were different (Saito et al 2019). The expectancy violation-based prediction was that if cats have a cross-modal representation of their owner they should pay attention to the monitor for longer in incongruent (mis-matching) conditions than congruent (matching) conditions.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, house cats -with a closer relationship with their owner -should show stronger results than cats living at a cat café where many people interact with them each day. In previous research data from these two groups of cats analyzed separately their responses to human voices were different (Saito et al 2019). The expectancy violation-based prediction was that if cats have a cross-modal representation of their owner they should pay attention to the monitor for longer in incongruent (mis-matching) conditions than congruent (matching) conditions.…”
Section: Introductionmentioning
confidence: 99%
“…They also discriminate between familiar and unfamiliar humans [16] and distinguish the voices of their owners from strangers [3]. A recent study has also shown that cats discriminate their own names from general words when pronounced both by their owner and unfamiliar persons [51]. However, to date, cat emotional communication with both conspecifics and humans has received limited attention.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, domestic cats have been shown to perform equally as well as dogs in object choice tasks using human pointing 25 , and only slightly worse than dogs in tasks that require human-directed attention-getting to obtain food 23 . Cats have also been shown to attract and manipulate human attention effectively in the auditory modality, through solicitation purring 26 , as well as discriminate their name from other words, even when unfamiliar humans are calling 27 . There is evidence that they also display specific facial actions during negative emotional contexts with humans compared to the same emotional contexts without human interaction 28 , 29 .…”
Section: Introductionmentioning
confidence: 99%